Cortical sources of resting state electroencephalographic rhythms differ in relapsing–remitting and secondary progressive multiple sclerosis - Babiloni, Claudio; Del Percio, Claudio; Capotosto, Paolo; Noce, Giuseppe; Infarinato, Francesco; Muratori, Chiara; Marcotulli, Christian; Bellagamba, Giovanni; Righi, Elena; Soricelli, Andrea; Onorati, Paolo; Lupattelli, Tommaso (Clinical neurophysiology, 2016)
•Resting state eyes-closed EEG activity was recorded in subjects with multiple sclerosis (MS) sub-types (phenotypes) such as relapsing–remitting (RR) and secondary progressive (SP).•Cortical sources of resting state EEG rhythms differ between RR and SP subjects.•Future studies should test the utility of these EEG markers in diagnostic and management of RR and SP subjects and in the therapy evaluation. Resting state electroencephalographic (EEG) rhythms are abnormal in multiple sclerosis (MS) patients, but it is unclear if they can reflect different neurophysiologic abnormalities in MS sub-types (phenotypes) such as relapsing–remitting (RR) and secondary progressive (SP). We tested whether cortical sources of resting state EEG rhythms are abnormal in MS patients and differ between MS phenotypes. Resting state eyes-closed EEG activity was recorded in 36 RR, 23 SP, and 41 matched healthy subjects. EEG bands of interest were individually identified based on Transition frequency (TF), Individual alpha frequency (IAF), and Individual beta frequency (IBF). LORETA freeware estimated cortical EEG sources. Widespread TF −4Hz (delta) and IAF (alpha) cortical sources were abnormal in the MS sub-groups compared to the control group. Furthermore, TF −4Hz sources in central, parietal, and limbic regions were higher in amplitude in the SP compared to the RR sub-group. Cortical sources of resting state EEG rhythms are abnormal in MS patients at group level and differ between RR and SP sub-groups. Future studies should test the utility of these EEG markers in the diagnosis and management of MS clinical phenotypes and in the therapy evaluation.